An Investigation of the Effectiveness of the 577- nm Pro-yellow Laser in Patients with Vascular Disorders - Ataseven, Arzu; Temiz, Selami Aykut; Özer, İlkay (European Journal of Therapeutics, 2023)
Objective: Vascular disorders severely impair the psycho-social status of individuals. Various laser and light systems, which have advantages and disadvantages, including the pro-yellow laser are used for the therapy of these disorders. Aim: The goal of the present study was to investigate the effectiveness and feasibility of the 577 nm pro-yellow laser for a broad range of indications including erythematelangiectatic rosacea, facial erythema, post-acne erythema, facial telangiectasis, hemangioma, genital angiokeratoma, and port wine stain nevus. Methods: A total of 98 patients (25 male, 73 female) older than 15 years who were treated with the pro-yellow laser for vascular disorders at the cosmetology unit between 2017 and 2019 were retrospectively included in the study. Results: The mean rate of recovery was 100% in genital angiokeratoma, 94.4% in spider angioma, 83.3% in facial telangiectasis, 74.8% in erythematotelangiectatic rosacea, 72% in facial erythema + facial telangiectasis, and 68.3% in facial erythema. Over 60% of improvement was observed in most patients with vascular disorders. There was no significant link between the Fitzpatrick skin type and treatment success. Treatment success was significantly low in cases with nasal involvement. Conclusion: The current study concluded that pro-yellow laser is an efficient and safe laser modality that may yield satisfactory outcomes regardless of the different skin types.